The effect of Apotel and Diclofenac suppository on pain relief after cesarean section among primiparous women: A randomized double-blind clinical trial study - Maryam Aradmehr; Marziyeh Lotfalizadeh; Morvarid Irani; Seyyedeh Adeleh Rahmanian; Mohammad Namazinia (Mashhad University of Medical Sciences, 2023)
Introduction: Inadequate pain control after caesarean can have adverse effects on various body systems, cause the mother not pay attention to the baby and problems in the breastfeeding process. Therefore, the present study was performed with aim to compare Apotel and diclofenac suppository on pain relief after cesarean section. Methods: This double-blind clinical trial study was performed in 2018 on 120 qualified primiparous women referred to Imam Reza and Pastor Hospitals in Mashhad. The subjects were randomly divided into two groups A and B (Apotel and diclofenac suppository). After cesarean delivery, if the mother requested for pain medication, group A received Apotel and group B diclofenac suppository. The severity of pain was assessed by McGill Pain Questionnaire before intervention, 6, 12 and 24 hours after cesarean section. Data were analyzed by SPSS software (version 16), and Mann-Whitney, t-test, Chi-square and Fisher exact tests. P<0.05 was considered statistically significant. Results: The two groups had no significant difference in the cesarean pain score before intervention (p=0.214), 6 hours (p=0.318), 12 hours (p=0.305) and 24 hours (p=0.117) after cesarean section. The mean of diclofenac suppository used in group A was 3.21±1.06 and the mean of Apotel used in group B was 1.02±1.22; the two groups were significantly different in the number of Apotel and Diclofenac used (p=0.048). Conclusion: Although there was no significant difference in the pain scores of the mothers in the Apotel and diclofenac suppository groups, the mean number of diclofenac suppository used was 3 times of Apotel used. Therefore, due to the longer effectiveness of intravenous acetaminophen and its safety compared to diclofenac, Apotel is recommended for cesarean section pain relief.